Metadena phoceae n. sp. (Digenea: Cryptogonimidae), a rectal parasite of the shore rockling Gaidropsarus mediterraneus (Teleostei: Lotidae) in the western Mediterranean - Bartoli, P.; Gibson, D. I. (Systematic Parasitology, 2001)
Metadena phoceae n. sp. is described and figured in detail from the rectum of the shore rockling Gaidropsarus mediterraneus (Lotidae) in the Gulf of Marseilles and off Corsica. It is compared with other cryptogonimids occurring in Mediterranean and Black Sea fishes and is distinguished from its closest relatives, M. depressa (Stossich, 1883) and M. pauli (Vlassenko, 1931), which occur in sparid and sciaenid fishes, respectively, by both morphometrical and biological features. The host-specificity of cryptogonimids occurring in Mediterranean and Black Sea fishes is commented upon.